2015
DOI: 10.1111/opo.12245
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ocular bulbar redness: a comparison of methods

Abstract: Digital imaging processing, using relative Red-channel activity, was the least variable of the three techniques. The R-scan and IER showed similar intra-observer variability. The linear relationship between R-scan and Red-value suggests that the R-scan could be derived using similar methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 35 publications
(83 reference statements)
1
29
0
Order By: Relevance
“…5A, Table 1). OR arises as a consequence of reactive dilation of conjunctival blood vessels (conjunctival hyperemia) and is a frequent response to diverse pathologic stimuli333435. When all controls and patients were considered, we detected a positive linear correlation between OR scores and conjunctival CD4 + T CM (r = 0.5; P  < 0.0001) and CD8 + T CM (r = 0.54; P  < 0.0001), and an inverse correlation with conjunctival CD8 + T EM (r = −0.4; P  = 0.0057) and T EMRA cells (r = −0.5; P  = 0.002) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5A, Table 1). OR arises as a consequence of reactive dilation of conjunctival blood vessels (conjunctival hyperemia) and is a frequent response to diverse pathologic stimuli333435. When all controls and patients were considered, we detected a positive linear correlation between OR scores and conjunctival CD4 + T CM (r = 0.5; P  < 0.0001) and CD8 + T CM (r = 0.54; P  < 0.0001), and an inverse correlation with conjunctival CD8 + T EM (r = −0.4; P  = 0.0057) and T EMRA cells (r = −0.5; P  = 0.002) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using infrared monitoring of the tear film, the Oculus algorithm documents the time and site of tear film breakup34. NI-TBUT value <10 secs was considered indicative of dry eye disease symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular redness is typically evaluated subjectively using grading scales in clinical practice . The literature has demonstrated that objective methods are more precise than subjective ones for evaluating conjunctival redness and may be better suited for research, to limit inter‐observer variability . In an attempt to define conjunctival redness more objectively, a new method previously described to measure blood oxygenation in small retinal blood vessels, was adapted for this protocol, using a photochromameter, which measures luminance reflectivity from the tissue being evaluated as well as the chromaticity of the reflected light in x, y co‐ordinates using the CIE 1931 chromaticity diagram .…”
Section: Methodsmentioning
confidence: 99%
“…The grading with the K5 is objective and stated to detect minor changes in redness (Downie et al, 2016). …”
Section: Ocular Surface Redness (Bulbar and Limbal Conjunctival Rednementioning
confidence: 99%